Impacts of Policy-Driven Transformation in the Livelihoods of Fishermen on Agricultural Landscape Patterns: A Case Study of a Fishing Village, Island of Poyang Lake - Minghui Ou; Yexi Zhong; Hongzhi Ma; Wenhui Wang; Manyu Bi (Land, 2022)
The agricultural landscape patterns of fishing village have undergone visible transformations in recent decades. Scholars pay less attention to fishermen with diverse livelihoods. Therefore, it is necessary to sort out the changing characteristics of fishermen’ livelihoods and agricultural landscape patterns under different policy periods. We use in-depth interviews, remote sensing technology, and mathematical analysis to systematically study the changes in fishermen’s livelihoods and in agricultural landscape patterns in a typical fishing village. The results show that policy have profoundly affected fishermen’ livelihoods. Livelihood transformation have altered local land use practices, which had a direct impact on agricultural landscape patterns. The livelihood of fishermen has changed from diverse to single, and their cropping structure were gradually becoming simpler and more specialised. After grazing ban and comprehensive fishing ban, many fishermen migrated to towns and cities, it accelerated the loss of population in the fishing village, which caused the amount of abandoned land increasingly. Left-behind fishermen became rice farmers by contracting abandoned paddy fields. The expanses of abandoned land and bamboo woodland had increased, which caused agricultural landscape patterns gradually becoming fragmented, heterogeneous and complex.